Cover of Buletin Pengabdian: Bulletin of Community Services (Bull. Community. Serv.) - Pengabdian, Buletin (Universitas Syiah Kuala, 2021)
Cover of BuletinPengabdian:Bulletin of Community Services(Bull.Community.Serv.)